1988
DOI: 10.1203/00006450-198808000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological and Biological Effects of Tin-Protoporphyrin on Neonatal Hyperbilirubinemic Gunn Rats

Abstract: ABSTRACT. Our study was undertaken to examine the pharmacological and biological effects of tin-protoporphyrin, a competitive inhibitor of heme oxygenase, on 5-or 6-day-old homozygous Cjlj) Gunn rats with hereditary unconjugated hyperbilirubinemia. When j / j neonates were injected subcutaneously with 20 pmol of tin-protoporphyrintkg of body weight, hepatic heme oxygenase activity decreased to 30% of the initial level 2 h after administration and remained low during the next 46 h. However, the reduction of ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

1989
1989
1993
1993

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…Our studies with jaun diced Gunn rats could confirm their findings [7][8][9] and also revealed that SnPP prevented jar syndrome). In fact, it has been reported that the administration of SnPP to a patient with Crigler-Najjar disease type I results in a reduction in the total plasma bilirubin con centration [6].…”
Section: Introductionsupporting
confidence: 79%
See 1 more Smart Citation
“…Our studies with jaun diced Gunn rats could confirm their findings [7][8][9] and also revealed that SnPP prevented jar syndrome). In fact, it has been reported that the administration of SnPP to a patient with Crigler-Najjar disease type I results in a reduction in the total plasma bilirubin con centration [6].…”
Section: Introductionsupporting
confidence: 79%
“…In fact, it has been reported that the administration of SnPP to a patient with Crigler-Najjar disease type I results in a reduction in the total plasma bilirubin con centration [6]. Unfortunately, the compound does not always appear to work well to control hyperbilirubinemia in human babies [5,6,12] and jaundiced Gunn rats [8]. Some of the SnPP-injected human babies remained high in the plasma bilirubin concentration, and hence they received phototherapy simulta neously [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…or greater [7,9,13]. In neonatal homozygous (j/j) Gunn rats who have severe unconjugated hyperbilirubi nemia due to a genetically determined ab sence of UDP-glucuronyl transferase for bil irubin, SnPP has been shown to prevent the marked increase in plasma levels of the bile pigment which occurs postnatally [26], In another study, mortality in Gunn rat neo nates was strikingly reduced by the adminis tration of a single dose of the compound [27], In addition a protective effect on bili rubin cerebellopathy was noted [27], In anemic mutant mice, with profound hemo lysis and anemia [red blood cell half-life reduced to «=¡2 days from the normal 60 days, 28] treated with extremely high doses of SnPP (100 pmol/kg b.w. once weekly for 8 months; cumulative dose/animal, 3,200 pmol/kg b.w.)…”
Section: Discussionmentioning
confidence: 99%
“…The potent inhibition by a synthetic ana logue of heme, namely, tin-protoporphyrin (SnPP), of heme oxygenase was reported by Drummond and Kappas [1], SnPP was shown to ameliorate jaundice significantly in animals [2,3] and human babies [4, 5], Un fortunately, the combination of treatment with SnPP and photoirradiation brought about cutaneous erythemata in human neo nates [4,5] and was lethal to rats [6,7], Cer tain modifications, such as irradiation with green light [8] and the use of compounds known as free radical scavengers [9], were proposed to protect babies from SnPP-induced phototoxicity. Efforts to identify non photosensitizing porphyrins with inhibitory effects on heme oxygenase have been made.…”
Section: Introductionmentioning
confidence: 99%